Faktor Determinan Anemia pada Mahasiswi Prodi D III Kebidanan STIKES Brebes - Ziyadatul Chusna Almabruroh Yuni Alfi (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Anemia is a condition where the level of red blood cells in a person's blood is lower than a normal person. Anemia can occur if a person's red blood cells do not have enough amount of haemoglobin. [4] In Indonesia, the prevalence of anemia by 57.1% is suffered by young women, 27.9% is suffered by women of reproductive age (WUS) and 40.1% is suffered by pregnant women. The main cause of nutritional anemia in Indonesia is the low level in iron intake (Fe). In adolescent women 26.50%, women of childbearing age (WUS) 26.9%, pregnant women 40.1%, and children under five 47.0%. [14] This study aims to determine the determinant factors of anemia in female college students. This research design uses descriptive analytic method. The sample in this study were all students of Study Program D III Midwifery of STIKES Brebes, amounting to 74 respondents. The data collection tool uses a portable HB check tool to determine HB levels and structured questionnaires. The results showed that as many as 31 respondents (41%) had anemia, most of which were 25 respondents (80.6%) knew well about anemia. A total of 11 respondents (35.4%) with normal menstrual cycles have anemia and 14 respondents (45%) live independently or boarding. Efforts should be made to carry out activities related to health education about the dangers of anemia and how to prevent it so that the incidence of anemia in young women students of the Midwifery Study Program of STIKES can be addressed properly.